Moral and Spiritual Perspectives in the Semantic Study of the Poem Da’il Ayyama Taf’alu Ma Tasya‘u by Imam Asy-Syafi’i - Hendar Ibnu Hajar; Mardi Hadi; Abdul Gofar Firdaus; Imam Asrofi (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
Research is a study of the elements that form poetry. In analyzing poetry, attention is usually paid to the relationship between lyrics in verses, the relationship between verses, intrinsic elements in verses, and the message conveyed by a poet, and includes the style of language used and the meaning contained in a poem. This study aims to analyze the aspects of lexical semantics and grammatical semantics in the poem by Imam Asy-Syafi'i entitled "Da'il Ayya>ma Taf'alu Ma> Tasya>‘u. The method used in this study is analytical descriptive research with a literature study approach to the analysis of lexical semantics in the meaning of individual words and grammatical semantics in the meaning of word structures. The results of the study indicate that this poem contains lexical meaning and grammatical meaning in strengthening the moral and spiritual messages of the contents of the poem. In terms of morals and ethics, this poem emphasizes noble values such as generosity and loyalty, which are the foundation of harmonious social relations and reflect strong faith, while in a spiritual context, this poem reminds us that everything in this world is ephemeral. Nouns such as "الأيام" (days), "حوادث الدنيا" (world events), and "المنايا" (death) emphasizes that worldly life is a journey full of trials and ends in certain death. Interrelated moral and spiritual values include patience, sincerity, generosity, justice, and awareness of the transience of the world. Keywords: Lexical semantic analysis, grammatical semantic analysis, Poetry Da'il Ayyama Taf'alu Ma Tasya'u, Imam Ash-Shafi'i.